Community Empowerment in Increasing the Added Value of Coconut Fruit (Cocos Nucifera L) into Transparent Soap in Pekanbaru City: Pemberdayaan Masyarakat Dalam Meningkatkan Nilai Tambah Buah Kelapa (Cocos Nucifera L) Menjadi Sabun Transparan di Kota Pekanbaru - Dewi, Ratna; Sehani, Sehani; Mardiah, Ainun; Emti, Desvi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to provide knowledge and practice to the community regarding the processing or process of coconuts into transparent soap products and to find out the packaging techniques for transparent soap products so that they have added value and are worth selling. The activity method carried out is using lecture and practice methods. The target audience for this community service are housewives in Pekanbaru City, which was held in Sidomulyo Timur Pekanbaru Village on June 29 2022, with a total of 50 participants. The method used in this activity is the Participatory Action Research method. The result of the service activity is that the stages of making transparent soap start from the stages of preparing the ingredients, weighing the ingredients, heating the ingredients, mixing (blending), stirring and finally printing. Participants can understand and practice making transparent soap made from pure coconut oil and make packaging for transparent soap products so that they are attractive and have sales value